Types and Frequencies of Pathologies in Endometrial Curettings of Abnormal Uterine Bleeding - Sarwar, Ayesha; Haque, Anwar ul (International Journal of Pathology, 2018)
Introduction: Abnormal uterine bleeding is one of the most frequently encountered and perplexing condition in adultwomen. Its causes include a wide spectrum of diseases. An important diagnostic method is endometrial curettage. Itprovides information regarding specific and nonspecific infections and malignancy. Histological evaluation can alsohighlight the incidental findings of organic causes as polyps or malignancy in cases in which no organic cause of bleedingwas initially suspected.Objective: The objectives of the study were to determine the types and frequencies of pathologies in endometrial curettingsof abnormal uterine bleeding & compare different endometrial pathologies in patient groups made according to age,presenting complaints and parity.Study Design: It was a comparative study.Setting: Histopathology department, Pakistan institute of Medical Sciences (PIMS), Islamabad.Material and Methods: H&E slides of endometrial curretings of 25 patients were evaluated. Diagnosis was madeby correlating the morphological findings with the clinical history over a period of one year i-e 14th Oct. 2004 to 14thOct. 2005Results: The most common complaint was polymennorhagia 36% (18/50) followed by mennorhagia 30% (15/50). Therewere two cases of oligomennorhoea (2%) and five cases of post menopausal bleeding (10%). Frequencies ofendometrial pathologies was Estrogen dominanance pattern 42% (21), Anovulatory endometrium and chronicendometritis 24% (12) each, atrophic endometrium and endometrial carcinoma 2% (1) each and 6% (3) cases of pill effectendometrium.Conclusion: Our study on endometrial curettings in abnormal uterine bleeding revealed clustering of cases aroundperimenopausal age. There was relative estrogen excess termed as Estrogen Dominance Pattern (EDP) overProgesterone leading to specific changes such as clusters of thickened blood vessels, spindly stroma, weak or absentsecretory changes in the glands and stroma with or without polyp formation. We also noted frequent anovulatory patternin the old age.